2019
DOI: 10.2337/db18-1076
|View full text |Cite
|
Sign up to set email alerts
|

Nine Amino Acids Are Associated With Decreased Insulin Secretion and Elevated Glucose Levels in a 7.4-Year Follow-up Study of 5,181 Finnish Men

Abstract: Several amino acids (AAs) have been shown to be associated with insulin resistance and increased risk of type 2 diabetes, but no previous studies have investigated the association of AAs with insulin secretion in a longitudinal setting. Our study included 5,181 participants of the cross-sectional METabolic Syndrome In Men (METSIM) study having metabolomics data on 20 AAs. A total of 4,851 had a 7.4-year follow-up visit. Nine AAs (phenylalanine, tryptophan, tyrosine, alanine, isoleucine, leucine, valine, aspart… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

12
106
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(118 citation statements)
references
References 25 publications
(22 reference statements)
12
106
0
Order By: Relevance
“…The four metabolites i.e., phenylalanine, alanine, palmitoylcarnitine and tyrosine were found consistently associated with the risk of T2DM. Another aliphatic AA called alanine is a hepatic substrate and stimulator for gluconeogenesis and glucagon secretion and its circulating amount was also found to be a predictive metabolite of T2DM risk in many cross-sectional and prospective studies [4,27]. Elevated levels of alanine have already been found to have a positive association with T2DM in Finland, UK, and South Asia populations, as stated above.…”
Section: Biomarkers Of Disturbed Protein Metabolismmentioning
confidence: 81%
See 1 more Smart Citation
“…The four metabolites i.e., phenylalanine, alanine, palmitoylcarnitine and tyrosine were found consistently associated with the risk of T2DM. Another aliphatic AA called alanine is a hepatic substrate and stimulator for gluconeogenesis and glucagon secretion and its circulating amount was also found to be a predictive metabolite of T2DM risk in many cross-sectional and prospective studies [4,27]. Elevated levels of alanine have already been found to have a positive association with T2DM in Finland, UK, and South Asia populations, as stated above.…”
Section: Biomarkers Of Disturbed Protein Metabolismmentioning
confidence: 81%
“…Moreover, the evident relationship of phenylalanine and tyrosine with the risk of T2DM was also significant due to an increase in insulin resistance through blocking the transport/phosphorylation of glucose. In the case of tyrosine, it is a far more powerful indicator of T2DM risk in South Asians [27]. The population-based KORA (Cooperative Health Research in the Region of Augsburg) and European Prospective Investigation into Cancer and Nutrition (EPIC)-Potsdam cohort study identified five baseline metabolites out of 131 (using pairwise comparison, multivariate (logistic) regression analyses followed by non-parametric random forest and the stepwise parametric regression) specifically associated with the pre-diabetic conditions to examine their ability to forecast the pre-diabetic conditions earlier [4].…”
Section: Biomarkers Of Disturbed Protein Metabolismmentioning
confidence: 99%
“…The other metabolites associated with the biomarkers included some that had been previously reported. Phenylalanine, which was associated with c‐peptide, was previously associated with insulin secretion and resistance . γ‐Glutamylglycine, which is the lead metabolite for a cluster that includes glycine, was inversely associated with both BMI and WC as well as CRP.…”
Section: Discussionmentioning
confidence: 95%
“…A recent study looking at amino acid concentration in 5181 non‐diabetic men aged between 45 and 73 years from the Finnish town Kuopio in relation with the development of type 2 diabetes found that a high L‐serine concentration is correlated to improved insulin secretion and sensitivity . L‐Serine is also associated with an improved glucose tolerance after a 2‐h oral glucose tolerance test, although no correlation was found to the development of type 2 diabetes.…”
mentioning
confidence: 99%